Wisata Desa dan Desa Wisata - Bagus Sudibya (Bali Membangun Bali: Jurnal Bappeda Litbang, 2018)
Village tourism in Indonesia is known as desa wisata which in English means tourism village. Gramatically the right one is the village tourism. That is why the two terms (wisata desa and desa wisata) is used synonimously in Indonesian context. This qualitative study found that the substance is that the village tourism is a business run by local villagers. So that, such kind of tourism is the one with the basic of community-based tourism or CBT. In Bali, the tourism itself as well as the CBT is a practice of paradigm which is popularly known as tri hita karana or THK. THK itself is a very basic concept in Bali which includes the relationships among God (parhyangan), people (pawongan), and environment (palemahan). The success of the village tourism depends on the succes of the THK implementation in such a tourism.